Factors associated with cesarean sections in a public hospital in Rio de Janeiro, Brazil Fatores associados à realização de cesáreas em uma maternidade pública do Município do Rio de Janeiro, Brasil - Eleonora D'Orsi; Dora Chor; Karen Giffin; Antonia Angulo-Tuesta; Gisele Peixoto Barbosa; Andréa de Sousa Gama; Ana Cristina Reis (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2006)
Brazil has one of the world's highest cesarean section rates. Contributing factors include the organization of obstetric practice, physicians' attitudes, and women's preferences and decisions. This study aimed to identify factors associated with cesarean sections in a public maternity hospital in Rio de Janeiro. A case-control study was conducted with 231 cesarean sections (cases) and 230 vaginal deliveries (controls). Hierarchical logistic regression analysis was performed, based on a conceptual model. Factors associated with increased odds of cesarean section were: primiparity; mother's age 20-34; last birth by cesarean; cervical dilatation < 3cm at admission; patient request; daytime birth; male attending obstetrician; obstetrician on duty for more than 24 hours a week; obstetrician with private practice; gestational hypertension; non-cephalic presentation; and gestational age > 41 weeks. Factors associated with lower odds of cesarean were: gestational age < 37 weeks; leaving home with signs of labor, use of oxytocin; and amniotomy. In this hospital, interventions aimed to modify the above-mentioned factors can help lower the cesarean rate. O Brasil apresenta uma das maiores proporções de cesáreas do mundo. Fatores contribuintes para este fenômeno incluem organização da prática obstétrica, atitudes dos obstetras, preferências e decisões das mulheres. Com o objetivo de identificar fatores associados à realização de cesáreas, foi realizado estudo de caso-controle em uma maternidade pública do Município do Rio de Janeiro. Incluíram-se 231 partos por cesárea (casos) e 230 partos vaginais (controles). Utilizou-se análise multivariada com regressão logística, as variáveis foram incluídas no modelo obedecendo à ordem hierárquica definida em modelo conceitual. Fatores associados à maior chance de cesárea: primiparidade; idade 20-34 anos; último parto por cesárea; dilatação cervical < 3cm na admissão; preferência da mulher por cesárea; horário diurno; parto realizado por obstetra do sexo masculino; obstetra que trabalha mais de 24 horas semanais de plantão; obstetra com consultório particular; hipertensão; apresentação fetal não-cefálica; e idade gestacional > 41 semanas. Fatores associados à menor chance de cesárea: prematuridade; sinais de trabalho de parto ao sair de casa; uso de ocitocina e amniotomia. Propostas de modificação nos fatores estudados podem contribuir para redução da proporção de cesáreas.